Multimodal Literacy and Visual Grammar in ESP Vocabulary Development: Insights from Air Force Training - Tran Hong Lam (Indonesian Journal of Linguistics, 2000)
Background: This action research study investigates the effectiveness of visual grammar and multimodal resources in teaching and learning specialised English vocabulary within the Air Force context, drawing on Kress and van Leeuwen’s visual grammar theory and Unsworth’s multimodal literacy framework. Purpose: The research examines how the compositional, interactive, and representational meanings of visual materials impact vocabulary acquisition and retention among Air Force personnel. Methods: The study analyses how visual design elements and multimodal resources support learning specialised Air Force terminology through iterative planning, implementation, observation, and reflection cycles. Python was used to automate the evaluation of visual materials against established criteria, providing an objective, data-driven analysis of their effectiveness. Data triangulation is achieved through three primary collection tools: semi-structured interviews with learners, classroom observation checklists focusing on learner engagement with visual materials, and vocabulary achievement tests measuring retention and comprehension. Results: The findings reveal how specific visual grammar elements influence vocabulary learning effectiveness, offering systematic criteria for selecting and designing visual materials in Air Force ESP instruction. Conclusion: This research contributes practical guidelines for implementing theoretically grounded visual choices in military ESP contexts while advancing understanding of the application of multimodal literacy in specialised vocabulary instruction.